Toleransi di Tengah Perbedaan Agama: Peran Kepala Dusun dan Tradisi di Desa Gajah Mati dalam Perspektif KKN Kelompok 58 UIN Fatmawati Sukarno Bengkulu - Ngadianto, Aprizal Wahyu; Juliastuti, Audri Aisa; Atmaja, Chandra Putra; Nengseh, Esy Sapitri; Susanto, Fadel Ilham; Maimunah, Maimunah; Najaria, Najaria; Aulia, Septi; Paramitha, Tiara Diva; Suryawan, Vonza Nabilla (PPSDP Undergraduate Journal of Educational Sciences, 2024)
The third batch of UINFAS Bengkulu’s mosque-based Community Service Program (KKN) has been completed by group 58 in Gajah Mati Village for approximately 40 days as a community service program. This activity not only aims to apply knowledge, but also to develop students’ social sensitivity and responsibility. This study uses observation, active participation, interview, and observation methods to analyze the phenomenon of tolerance in the community. The main focus of this study is on religious tolerance in Hamlet II, where the head of the hamlet is Catholic while the majority of the community is Muslim. Although there are differences in beliefs, religious tolerance in this village is very much maintained. The results show that religious differences do not become a barrier, but rather strengthen harmony and togetherness in the village. In addition, local traditions such as Friday Kliwon Night Prayer and Ambengan are still maintained by the local community, reflecting strong values of togetherness and spirituality. This study emphasizes the importance of tolerance and tradition preservation in maintaining social harmony in a multicultural society.